Recursos Didácticos en el proceso de enseñanza aprendizaje de lengua y literatura en los estudiantes de básica elemental de la Unidad Educativa “República de Alemania”, cantón Buena Fe. - Tumbaco Castro, Miriam Maribel (2017)
The main objective of this project is to make teachers aware of the importance of the elaboration, manipulation and use of didactic resources in the area of language and literature at the time of imparting new knowledge to students. Education in Ecuador is one of the fundamental objectives that the State has in which it is improved, the purpose is to provide a quality education, free of charge in which all Ecuadorians benefit from regardless of gender, age, or race. The present research carried out in the Educational Unit "Republic of Germany" arises from the need for teachers to become aware of the importance of the use of didactic resources to improve teaching - learning in language and literature, the lack of didactic resources, it becomes monotonous and of little interest to learners. In current education some teachers have maintained traditional education, in the learning process, they have not used any didactic resource that allows an active activity, and do not develop skills or achieve significant learning because they do not have knowledge and have no knowledge of their use. of the teaching resources. These shortcomings lead to a delay in the education of students, not only in the area of language and literature, but in subjects in general, because students have problems reading or understanding texts that cause them to be delayed. To achieve the above, it is convenient and necessary to apply innovative techniques and procedures that call the student's attention motivating him to continue in his studies. Currently, the educational system requires the teacher to use necessary skills, techniques and didactic resources in order to contribute to the improvement of the country's education system.